2021
DOI: 10.3389/fsoil.2021.719651
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Dynamics in Sugarcane Fertilized With Filter Cake and Mineral Phosphate Sources

Abstract: Organic residual material such as filter cake, combined with mineral phosphate fertilizers, may alter the soil phosphorus (P) bioavailability for sugarcane as a consequence of the competing effect in adsorption sites. This study aimed to quantify the changes in both the inorganic and organic soil P fractions as amended by phosphate fertilizer sources and filter cake and to link the P fractions to sugarcane response. An experiment was conducted in an Oxisol, in a randomized block design with factorial arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
2
0
3
Order By: Relevance
“…Some studies on sugarcane have highlighted the effects of applying filter cake as a source of P because it favors the physiological and nutritional aspects of the crop [31,60,61].…”
Section: Results Of the Application Of Filter Cake To The Soil And In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on sugarcane have highlighted the effects of applying filter cake as a source of P because it favors the physiological and nutritional aspects of the crop [31,60,61].…”
Section: Results Of the Application Of Filter Cake To The Soil And In...mentioning
confidence: 99%
“…Filter cake, combined with phosphate mineral fertilizers, can alter the bioavailability of P from the soil to sugarcane plants due to the competitive effect on soil P adsorption sites. Thus, Soares et al [60], while assessing changes in soil organic and inorganic P fractions induced by phosphatic fertilizers in the presence and absence of filter cake, observed that this material, serving as a nutrient and organic matter source, plays a crucial role in maintaining more P available for plant uptake, especially when associated with the triple superphosphate fertilizer compared to Araxá natural phosphate and Bayóvar ® reactive phosphate.…”
Section: Results Of the Application Of Filter Cake To The Soil And In...mentioning
confidence: 99%
“…Na literatura existem ensaios demonstrando formas mais eficientes de maximizar a utilização de adubos fosfatados, evitando desperdícios por meio das aplicações desenfreadas o qual grande parte pode ser perdida via fixação. Nesse contexto, de Aquino et al (2021) objetivaram quantificar as alterações na dinâmica de disponibilidade de fósforo em cana de açúcar, mediada pela aplicação de torta de filtro e adubos inorgânicos. Portanto, os autores realizaram as adubações utilizando três fontes de fósforo inorgânico: superfosfato tripo (TSP) (44% do P 2 O 5 e 41% solúvel em ácido cítrico a 2%), fosfato de rocha Araxá (ARP) ( 22% do P 2 O 5 e 4% solúvel em ácido cítrico a 2% ) e Bayóvar® fosfato reativo (BRP) ( 28% do P 2 O 5 e 14% solúvel em 2% de ácido cítrico, aliado a presença e a ausência da torta de filtro (7,5 t ha -1 massa seca), a qual as fontes inorgânicas foram aplicadas na fase de plantio na dose de 90 kg ha -1 P 2 O 5 .…”
Section: Adubação Fosfatadaunclassified
“…Marrocos) e a utilização de microrganimos solubilizadores e mineralizadores de P, vem sendo amplamente estudadas e têm se mostrado alternativas promissoras para o uso mais eficiente do nutriente (Soares et al, 2021;Rosa et al, 2020;Soltangheisi et al, 2019;.…”
Section: Bayovar Eunclassified
“…Além dessas, outras práticas que vem sendo amplamente estudadas são o uso de fontes menos solúveis de P, como o fosfato natural reativo (e.g. Bayovar e Marrocos) e fontes orgânicas como a torta de filtro, assim como a utilização de bioestimulantes compostos por microrganimos solubilizadores e mineralizadores de P (Soares et al, 2021;Rosa et al, 2020;Soltangheisi et al, 2019;.…”
Section: Fósforo: Importância Para Plantas E Dinâmica No Solounclassified